HERITAGE OF STATE DOCUMENTATION: THE ASPECT OF DOCUMENT AND ARCHIVES MANAGEMENT - LUKŠAITĖ, DAIVA (Knygotyra, 2012)
Since the forms of documents and the technologies of their management are changing, the functions performed by archives institutions are being reconsidered and reassessed. Archivists having been involved into the process of document management from the very beginning of document creation, an opportunity has occurred to sequentially match the decisions of selecting and storing of documentation which has an influence on both the conception of archival functions and the formation of documentary or archival heritage. In the sphere of documentation and archives management, heritage is related to the documentation (cultural values), which is a source of collective memory and scientific information; these documents are a meaningful historical certification. This fact emphasizes the importance of the three factors – memory, documentation and archives management – in achieving the goals of archival heritage with the help of their functions.The documentation continuum mo del reveals document identification, its importance as a source of memory and on the whole the evaluation of archives in a wider social context as well as archives accessibility to society. This model as well as the conception of both documentation and archives management are analyzed in the article with reference to the works of foreign archives researchers. The article also aims to answer such questions as what is distinct in documentation and archives management, what is the benefit of such management, and how documentation and archives management is understood in Lithuania. The search for these answers is meaningful, as the structural reconstruction of public sector institutions in Lithuania is inseparable from the reconsideration of the functions of archives institutions. That is why the article demonstrates what archives functions are distinguished and what are used for the sake of archives heritage as well as what should be changed while performing such functions in Lithuanian state archives.
Keywords: ...